Monitoring population changes in the rhizosphere of a range of hydroponic tomato crops, featuring various water treatment methods across the 2014/2015 growing season - Bagley, Stuart (2016)
A member of the solanaceous family of plants, tomato is the eighth most economically important agricultural product, and the fourth most economically important crop worldwide with around 164 million tonnes produced yearly. Europe dominates the highest yielding production systems, with the UK being the third highest yielding producer worldwide. Much of the modern day British production uses soilless systems housed in glasshouses. Glasshouses allow for greater control over the environmental factors that affect production, from pests and diseases, to temperature fluctuation and water scarcity. Using a soilless system adds to the control the grower has over the crop production, being able to adjust water and nutrient supply as and when needed. However, due to environmental impacts and high costs, it is becoming common to use a recirculating water system, rather than systems where the water runs to waste. With this closed system approach, issues arise regarding the recirculation, and the potential for rapid dispersal of potentially pathogenic organisms amongst whole crops. This can have obviously devastating effects upon grower’s production and therefore it is now common place for growers to incorporate a water treatment step to remove such organisms or at least reduce their abundance. In this research, microbial populations were monitored at separate points throughout commercial tomato production systems, at quarterly time points throughout the season. The populations were assessed by means of a small scale microarray, developed to contain probes targeting organisms commonly associated with commercially grown tomato rhizospheres. Five commercial nurseries were monitored through the season, each featuring contrasting water treatment systems; pSSF (part slow sand filter), fSSF (full slow sand filter), heat treated, UV treated and a final nursery that was instead an open system using a RTW (run to waste) method. Nurseries each supplied five water sample sets from separate sampling points throughout the loops, as well as a set of root samples at each quarterly sampling point. On top of this, five more nurseries supplied root samples at two time points. The first aim of the research was to monitor the population changes as the water passes through each system loop, including a pre and post treatment sample. The second aim of the research was to monitor the microbial population changes associated with the roots of each system throughout the season and build a base of knowledge of the common trends and features of the population through the year and if the treatments affected this. The final research aim was to develop and validate a range of qPCR assays for four commonly detected pathogens; Colletotrichum coccodes, Plectospharella cucumerina, Pythium aphanidermatum and Pythium myriotylum. Many differences were demonstrated in the water samples throughout the various systems. The RTW system exhibited the lowest species richness of them all, whilst the fSSF exhibited the highest. In each system, peak species richness was usually found in either the slab solution samples or from the pre-treatment samples. From the species diversity scores, all treatments seemed to result in a reduction in diversity following treatment, and upon further inspection both pSSF and fSSF systems exhibited a significant difference. Throughout the season, two bacterial species Nitrospira and Pseudomonas were commonly detected as well as a range of Pythia species. From the root observations, again the Pythia were very common, as was Nitrospira, Pseudomonas, Xanthomonas and Erwinia. These were common across the five main nurseries as well as the additional nurseries. Most systems throughout the season showed a general decline in abundance of species towards the end. Again, the fSSF system scored the highest species richness, whilst the heat treated nursery featured the lowest species richness. In the RTW system, two crops were grown, a crop on non-grafted roots, and another on a grafted rootstock. It was found that over the season the grafted roots, despite starting with higher species richness, had a reduced organism number on their roots, and also in the water. Finally, for the q-PCR assays developed, both the C. coccodes and the P. cucumerina assays were successfully validated and tested and showed positive results, whilst the P. aphanidermatum and P. myriotylum assays also showed promising results in their preliminary tests. Unfortunately the latter two assays could not be tested further due to time constraints. From the findings of this research it was realised that it is important to use the microarray in conjunction with other techniques, and that the microarray should not be used alone to infer causality. As well as this, organisms such as Pythia were found to be consistently prevalent, across systems, sample types and the season. Further research should be carried out to characterise their habits and develop methods to effectively reduce their prevalence throughout the season. On top of this, samples from the system utilising the fSSF water treatment system generally yielded the highest species richness over the season whilst the pSSF seemed more effective at reducing this number. Little is known about the way in which SSF systems work, in terms of if they are a physical treatment or biological, and these results emphasise their complex attributes. Further research is needed into the organisms that may inhabit the filters, and whether potentially pathogenic species will remain dormant in them between seasons.